Educational e-accountability: Lessons for Zimbabwe's educational accountability system - Shepherd Shoko (Rafandha Press, 2025)
Background: Zimbabwe still relies on a traditional educational accountability system that can no longer cope with new pressures for educational accountability in the face of changing conceptions and practices of Educational Accountability. This prompted the researcher to explore a possible alternative of an educational accountability system driven by technology Method: Educational e-accountability systems in three countries were analysed to draw lessons for Zimbabwe's proposed educational e-accountability system. The researcher employed a qualitative approach using the content analysis technique. The focus was on some online studies purposively selected and derived from the EBSCOHOST, JSTOR, ProQuest E-Book Central and Google web search engine. The paper exposed the inadequacies of Zimbabwe’s current educational accountability system, which is described as traditional, limited, and weak in feedback mechanisms as compared to accountability systems of the other three countries, namely the United States of America, Australia, and Botswana. Findings: The proposed e-accountability for Zimbabwe, unlike other countries reviewed that rely on one form of accountability, draws from external and internal accountability systems informed by Open Government concepts to maximize the combined strengths of these three conceptual frameworks. If implemented, the new e-accountability system will improve accountability, efficiency, effectiveness, trust, transparency, feedback, and ultimately, the educational outcomes in Zimbabwean schools.